Caracterización fisicoquímica del agua generada en el proceso de desamargado del chocho (Lupinus mutabilis Sweet), mediante el método tradicional, en el campus experimental ceasa de la universidad técnica de Cotopaxi, cantón Latacunga en el período 2020 – 2021. - Chaluisa Guanotuña, Jessica Myreya (2021)
During the last decades a potential demographic growth is evident; therefore, a depletion of resources and spaces that reveal a constant degradation of ecosystems such as rivers, which receive illegal discharges without prior treatment as a result of industrial processes such as the previous procedure to consume certain foods. For instance, the Lupinus mutabilis, Sweet (lupine), it is a nutritious, healthy and natural food. This Andean grain has as its main obstacle that is the presence of alkaloids, which are toxic and have a bitter taste; thus, the need arises to remove them through a debittering process for human consumption. The following research is focused on the physicochemical and microbiological characterization of the water used in the subprocesses of lupine debittering by the traditional method, which was carried out in the laboratories of the Technical University of Cotopaxi, Salache campus. In other words, it is about a general diagnosis of the water quality indicators,the efficiency of the debittering method in the two varieties (INIAP 450 ANDINO and INIAP 451 GUARANGUITO) and two ecotypes (Peruvian Ecotype and Native Local Ecotype) for the two dry-tender maturity indices by taking into account the percentage of alkaloids present in each debittering sub-process (hydration, cooking and washing) with an environmental focus on the alternatives of savings in water consumption and its reuse; consequently, avoiding clandestine discharges with high levels of alkaloids. Through design in test phase, an analysis of variance was carried out from simple samples of each debittering sub-process where the physicochemical and microbiological characteristics xiv were determined. According to the data obtained, the corresponding analysis was carried out for each parameter of pH, temperature, dissolved oxygen, turbidity, BOD5, COD and dissolved, suspended and total solids. The comparison between the two varieties and two ecotypes of the dry-tender maturity indices, determine which of these reports data within the Maximum Permissible Limits described in the current environmental regulations "Unified Text of Secondary Environmental Legislation" (TULSMA) considering the quality criteria for discharges to a public sewer system. The results reported data indicating a higher concentration of pollutant load in the water of the cooking sub-process due to the alkaloid removal capacity as far as it was exposed to a temperature of 90ºC for 30 minutes, all the parameters presented this alteration. As a result of the difference between the two maturity indices, tender lupine tends to eliminate alkaloids faster with 9 washes compared to dry lupinewith 12 washes